Analisis Kemampuan Berpikir Kreatif Matematis Siswa pada Materi Transformasi Geometri - Rizqi, Muhammad; Nurjali, Nurjali (AB-JME: Al-Bahjah Journal of Mathematics Education, 2023)
Students' Creative Thinking Ability can be developed through the learning process at school, the way that is done is to provide description questions that can reveal creative thinking abilities. This study aims to explore examples of students' creative thinking skills which can be used as a stimulus to improve their abilities. This type of research is descriptive research, with data collection techniques obtained through literature studies (thesis, textbooks, journals) as well as primary data obtained through experiments. The steps for data collection are carried out by giving students a set of examples of creative thinking ability test questions with adjusted material coverage based on indicators of creative thinking ability. The results showed that the students' creative thinking ability as a whole was included in the medium category.